Sliding doors: how does their opening affect particulate matter levels in operating theatres? - Della Camera, Alessandro; Cevenini, Gabriele; Nante, Nicola; De Marco, Maria Francesca; Messina, Gabriele (International Journal of Infection Control, 2022)
Background: Operating theatres (OTs) have adequate conditions to perform safe operations and to prevent surgical site infections (SSIs). Opening doors can compromise these situations. Measurement of particulate contamination is a crucial point to check the effectiveness of preventive measures in the OTs. We analysed how opening the doors interact with particulate contamination in different designs of OTs. Methods: Between January and February 2020, a cross-sectional study was conducted in five different types of OTs of a teaching hospital in Siena. Two (OTs 1 and 2) had laminar flows, with 58 and 55 air changes/h, respectively. Three had turbulent flows: OT3 (18 air changes/h, with four inlets from the ceiling), OT4 (16 air changes/h, airflow directed from one wall to the opposite one and the main door laterally to the flow) and OT5 (23 air changes/h and airflow from the ceiling plenum). Particulate matter (PM) measurements were carried out at seven different locations in each OT, alternating two conditions: 1) doors closed and 2) opening/closing the main door twice per minute. For each spot, in each condition, we recorded for several minutes the following parameters: particles (>0.3, >0.5, >1, >3, >5 and >10 µm), room temperature (RT), relative humidity (RH) and airflow velocity (AS). International Organization for Standardization (ISO) class for PM > 0.5 µm was calculated. Comparison with the Wilcoxon signed-rank test was made using Stata 16 (StataCorp LLC, College Station, TX, USA). Results: All five OTs had differential pressure, but all fell to 0 at door opening; negligible changes were detected on microclimatic parameters although they may be affected by different types of airflows and design. Even though the variations in the turbulent flow rooms were broader and different, there were no changes in ISO class particle classification, given the already very high initial particulate levels. In laminar flow rooms, with a better ISO classification, the variations were smaller but sufficient to worsen the class. Conclusions: When opening the doors, the PM levels in OTs are influenced by different ventilation systems and room design. Different ventilation systems and the design of OTs influence particulate levels during door opening. Particulate variations in the laminar flows studied were smaller than in the turbulent flows, which, although lower in performance in our study, can be just as effective; however, as the heterogeneous construction and logistic characteristics of OTs result in significant variations in PMs, further research is needed to determine the actual effect of airflow on the SSI rate.